Analysis of the Contribution of Arm Muscle Strength and Leg Muscle Explosive Power in Students to their Smash Ability in Volleyball Games - Ifan Badra Wijaya; Agung Wahyudi; Bayu Murti Suryonegoro (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The importance of arm muscle strength and leg muscle explosive power in contributing to volleyball smash ability prompted researchers to analyze their magnitude in relation to student or athlete achievement in volleyball learning, which is part of the physical education curriculum program. Methodology: This type of research is quantitative, using a correlational approach with a quasi-experimental method. The population in this study were volleyball athletes with a sample of 20 athletes. The instruments used in this research were the hanging elbow test, vertical jump test and smash ability test. Meanwhile, this research data analysis technique uses statistical data analysis through linearity and correlation tests. Main Findings: Based on the research results, it was found that arm muscle strength and leg muscle explosive power make a significant contribution and have a big influence on the smash ability of athletes or students. Therefore, these findings require follow-up regarding the development of innovative teaching resources, such as textbooks or monographs, as a step to improve an athlete's or student's smashing ability in the volleyball learning process, thereby increasing students' motivation and learning outcomes. Novelty/Originality of this study: This research provides an in-depth analysis of the athlete's arm muscle strength and leg muscle explosive power on their smash ability by designing a training program and strategy that are more effective and suitable for improving volleyball smash ability.